Hands-on with Vista Service Pack 2 Beta. - Mediati, Nick
Windows Vista Service Pack 2 promises some significant improvements, including adding the ability to record data onto Blu-ray discs. It includes instructions on how to install the SP2 and features such as more-efficient sidebar and Blu-Ray burning.
Keywords: Windows Vista SP2.